Sequence and exon-intron organization of the DNA encoding the alpha I domain of human spectrin. Application to the study of mutations causing hereditary elliptocytosis. - Sahr, K E (1989)
We have determined the exon-intron organization and the nucleotide sequence of the exons and their flanking intronic DNA in cloned genomic DNA that encodes the first 526 amino acids of the alpha I domain of the human red cell spectrin polypeptide chain. From the gene sequence we designed oligonucleotide primers to use in the polymerase chain reaction technique to amplify the appropriate exons in DNA from individuals with three variants of hereditary elliptocytosis characterized by the presence of abnormal alpha I spectrin peptides, 46-50 and 65-68 kD in size, in partial tryptic digests of spectrin. The alpha I/68-kD abnormality resulted from a duplication of leucine codon 148 in exon 4: TTG-CTG to TTG-TTG-CTG. The alpha I/50a defect was associated in different individuals with two separate single base changes in exon 6: CTG to CCG (leucine to proline) encoding residue 254, and TCC to CCC (serine to proline) encoding residue 255. In another individual with the alpha I/50a polypeptide defect, the nucleotide sequence encoding amino acid residues 221 through 264 was normal. The alpha I/50b abnormality resulted from a single base change of CAG (glutamine) to CCG (proline) encoding residue 465 in exon 11 in two unrelated individuals. In a third individual with alpha I/50b-kD hereditary elliptocytosis, the entire exon encoding residues 445 through 490 was normal. The relationship of the alpha I domain polypeptide structure to these mutations and the organization of the gene is discussed.